eNOS S-nitrosylates β-actin on Cys374 and regulates PKC-θ at the immune synapse by impairing actin binding to profilin-1. - Almudena García-Ortiz; Noa B Martín-Cofreces; Sales Ibiza; Ángel Ortega; Alicia Izquierdo-Álvarez; Antonio Trullo; Víctor M Victor; Enrique Calvo; Begoña Sot; Antonio Martínez-Ruiz; Jesús Vázquez; Francisco Sánchez-Madrid; et al. (PLoS Biology)
The actin cytoskeleton coordinates the organization of signaling microclusters at the immune synapse (IS); however, the mechanisms involved remain poorly understood. We show here that nitric oxide (NO) generated by endothelial nitric oxide synthase (eNOS) controls the coalescence of protein kinase C-θ (PKC-θ) at the central supramolecular activation cluster (c-SMAC) of the IS. eNOS translocated with the Golgi to the IS and partially colocalized with F-actin around the c-SMAC. This resulted in reduced actin polymerization and centripetal retrograde flow of β-actin and PKC-θ from the lamellipodium-like distal (d)-SMAC, promoting PKC-θ activation. Furthermore, eNOS-derived NO S-nitrosylated β-actin on Cys374 and impaired actin binding to profilin-1 (PFN1), as confirmed with the transnitrosylating agent S-nitroso-L-cysteine (Cys-NO). The importance of NO and the formation of PFN1-actin complexes on the regulation of PKC-θ was corroborated by overexpression of PFN1- and actin-binding defective mutants of β-actin (C374S) and PFN1 (H119E), respectively, which reduced the coalescence of PKC-θ at the c-SMAC. These findings unveil a novel NO-dependent mechanism by which the actin cytoskeleton controls the organization and activation of signaling microclusters at the IS.